Influence of exercise intensity on skeletal muscle blood flow, O(2) extraction and O(2) uptake on-kinetics - Jones, Andrew M (Blackwell Science Inc, 2012)
Following the start of low-intensity exercise in healthy humans, it has been established that the kinetics of skeletal muscle O(2) delivery is faster than, and does not limit, the kinetics of muscle O(2) uptake ([Image: see text]). Direct data are lacking, however, on the question of whether O(2) delivery might limit [Image: see text] kinetics during high-intensity exercise. Using multiple exercise transitions to enhance confidence in parameter estimation, we therefore investigated the kinetics of, and inter-relationships between, muscle blood flow ([Image: see text]), a–[Image: see text] difference and [Image: see text] following the onset of low-intensity (LI) and high-intensity (HI) exercise. Seven healthy males completed four 6 min bouts of LI and four 6 min bouts of HI single-legged knee-extension exercise. Blood was frequently drawn from the femoral artery and vein during exercise and [Image: see text], a–[Image: see text] difference and [Image: see text] were calculated and subsequently modelled using non-linear regression techniques. For LI, the fundamental component mean response time (MRT(p)) for [Image: see text] kinetics was significantly shorter than [Image: see text] kinetics (mean ± SEM, 18 ± 4 vs. 30 ± 4 s; P < 0.05), whereas for HI, the MRT(p) for [Image: see text] and [Image: see text] was not significantly different (27 ± 5 vs. 29 ± 4 s, respectively). There was no difference in the MRT(p) for either [Image: see text] or [Image: see text] between the two exercise intensities; however, the MRT(p) for a–[Image: see text] difference was significantly shorter for HI compared with LI (17 ± 3 vs. 28 ± 4 s; P < 0.05). Excess O(2), i.e. oxygen not taken up ([Image: see text]×[Image: see text]), was significantly elevated within the first 5 s of exercise and remained unaltered thereafter, with no differences between LI and HI. These results indicate that bulk O(2) delivery does not limit [Image: see text] kinetics following the onset of LI or HI knee-extension exercise.